Relationship Status and Sexual Behaviors in Post-Pelvic Inflammatory Disease (PID) Affected Urban Young Women: A Sub-Study of a Randomized Controlled Trial - Tabacco, Lisa (Int Arch Nurs Health Care, 2018)
Adolescent and young adult women disproportionately experience Pelvic Inflammatory Disease (PID) as a complication of Sexually Transmitted Infections (STIs). This study seeks to understand the relationship context, changes in sexual behavior, and impact of partner sexual behavior on recurrent STI diagnoses at 3-months post-diagnosis. Adolescents and young adult women 13–25 were recruited from an outpatient disposition from an outpatient clinic, and pediatric and adult emergency rooms. Participants received treatment at baseline and follow-up at 2-weeks, 1-month and 3-month post-diagnosis, including interviews about personal and partner sexual behaviors and STI screening (n = 94). At the 2-week interview, 53% of participants (50/94) believed they could acquire an STI from their current partner if they did not use a condom. However, at 3-month follow-up only 35% reported condom usage at last sex. At 3-month follow-up, 55% (50/91) of participants were still in a sexual relationship with the previously reported partner and 38% of participants who reported they could get an STI from their partner were diagnosed with an STI; compared with 25% of participants who predicted that they could not get an STI (OR 1.85; 95% CI: 0.67–5.30). There was no association between maintaining the same partner and having an STI at 3-months (OR 0.5; 95% CI: 0.27–1.96). Most young women diagnosed with PID report exclusive relationships, but are simultaneously aware of their risk for recurrent STIs. Given the short-term stability of many relationships, couples interventions are an unexplored opportunity for prevention of recurrent STIs after PID.